Atmospheric methane and carbon dioxide concentrations measured during ALKOR cruise AL575 on 2022-07-02 - Tim Weiß; Mark Schmidt; Matthias Haeckel (PANGAEA, 2025)
Atmospheric carbon dioxide (CO2) and methane (CH4) concentrations were monitored during AL575 cruise on 2022-07-02 using a cavity ring down spectrometer (Picarro G2301-f CRDS) and GEOMARs extquotesingleAtmospheric Intake System extquotesingle (AIS). The Picarro/AIS system was installed in the wet laboratory (starboard, main deck) of RV ALKOR and was connected by an aluminium tube to an air inlet nozzle placed at the bow of RV ALKOR. The air was pumped via the AIS intake tube with a flow rate of 2.67 litre per minute to the Picarro analyser. The atmospheric CH4, CO2, and water vapour concentrations were determined in real time at 2-3 Hz sampling rate. A time offset of 87 seconds between the air intake nozzle at the bow (6 m above sea surface) and the actual gas measurement at the Picarro was determined and the calculated flow rate considered, when correlating the gas data with navigation and weather data provided by the WERUM dship repository (https://dship.geomar.de). The weather data is published separately at doi:10.1594/PANGAEA.983833 .
In: Weiß, T et al. (2025): Atmospheric methane and carbon dioxide concentrations measured during ALKOR cruise AL575, 29 June 2022 – 12 July 2022, Kiel – Kiel [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.982665